INFLUENCE OF GROWTH ZONES ON THE PHYSICAL CHEMICAL COMPOSITION OF THE FRUIT OF Solanum betaceum Cav. - Navarro Huaynates, Arturo A. (2018)
In the present research, the fruit of the tomato sacha (Solanum betaceum Cav.) From two zones of the Cajamarca region was evaluated, a morphological, compositional, proximal, mineralogical and phytochemical profile was evaluated. The average results of the analyzes were: morphological the proportion of pulp 79,81 %, seed 13,13 %, husk 6,22 %; the average weight of the fruit was 75,61 g; with respect to the dimensions of the fruit we have: length 65,23 cm and width 40,17 cm; According to cielab method the color of the fruit is yellowish red; the hardness of the pulp was: -1,75 Lb; 84,45 % moisture content; ash of 1,02 %, proteins of 2,02 %, lipids 0,065 %, crude fiber of 8,03 %, nitrogen-free extract of 4,37 % and soluble solids of 9,83 ° Brix. Metabolites were identified as: free amino acids, tannins, flavonoids, leucoanthocyanidins and alkaloids. The average content of polyphenols was 96,915 mg EAG / 100g of pulp and the average flavonoid content was 158.64 mg EQ / 100 g of pulp. In the mineralogical profile the presence of Na, K, Ca, Mg and P stands out; Fe, Cu, Zn, Mn, B and Si.